Bibliometric Analysis of Research on Factors Affecting Service Quality and Physician Performance - Marlina Marlina; Iwan Aflanie; Izaak Zoelkarnain Akbar; Muhammad Abdan Shadiqi; Ardik Lahdimawan (Universitas Malahayati Lampung, 2024)
ABSTRACTThis study analyzes the influence of various factors on service quality and doctor performance with a focus on aspects of additional employee income, adequacy of doctor personnel, facilities and infrastructure, competence, and communication. The background of this study is the importance of improving the quality of health services to achieve optimal patient satisfaction and effective physician performance. The purpose of this study is to identify trends, distribution, and relationships between these factors in the scientific literature, as well as identify research gaps that need to be further explored. The method used in this study is bibliometric analysis, with data collected from Google Scholar using the Publish or Perish application. The search period was limited to 2018 to 2024, and the keywords used included